The gift of pain with transformative possibilities - Richard Hovey (The Beryl Institute, 2018)
This personal narrative explores the experiences of pain metaphorically as a gift. The intention of this article is to offer alternative ways to reflect on pain, life and taking risks to move from health literacy toward health agency with help. I describe my approach to decision making using the hermeneutic wager which provides a means to imagine possibilities while mindfully assessing risk. Learning to manage pain and learning to live well with pain is a gift that we are not always aware is within our grasp.